Effect of antioxidant, malondialdehyde, macro‐mineral, and trace element serum concentrations in Bangladeshi patients with schizophrenia: A case‐control study. Issue 2 (11th May 2021) - Uddin, S. M. Naim; Sultana, Farhana; Uddin, Md. Giash; Dewan, Syed Masudur Rahman; Hossain, Mohammed Kamrul; Islam, Mohammad Safiqul
Abstract: Background: Schizophrenia (SCZ) is an incurable neuropsychiatric disorder generally described by impaired social behavior and altered recognition of reality. For the first time, this study explored serum levels of antioxidants (vitamin A, E, and C), malondialdehyde (MDA), macro‐minerals (calcium, potassium, and sodium), and trace elements (zinc, iron, and selenium) in Bangladeshi patients with SCZ and thereby, discovering any pathophysiological correlation. Methods: This case‐controlled study evaluated 63 patients with SCZ as cases and 63 healthy individuals as controls. Vitamin A and E levels were defined by RP‐HPLC. MDA and vitamin C levels were measured by using UV spectrophotometry, and macro and trace elements by atomic absorption spectroscopy. Results: This study found significantly ( P  ≤ 0.05) elevated MDA levels and decreased levels of antioxidants—vitamin A, C, and E and significantly ( P  ≤ 0.05) diminished levels of macro and trace elements in cases in contrast to the controls. Serum levels of zinc (Zn), selenium (Se), iron (Fe), potassium (K), calcium (Ca), and sodium (Na) were determined to be 0.33 ± 0.008, 0.0252 ± 0.00060, 0.24 ± 0.01, 64.18 ± 2.72, 36.88 ± 2.56, and 2657.5 ± 53.32 mg/L, respectively, in cases, whereas 0.79 ± 0.03, 0.0650 ± 0.00355, 0.78 ± 0.03, 168.01 ± 2.85, 86.43 ± 2.55, and 3200.8 ± 29.96 mg/L, respectively, were determined in controls. Pearson's correlation analysis revealed a negative correlation between Zn and Na, Zn and K, Zn and Ca, Zn and Fe, Zn and Se, Fe and Na, and Fe and Se in patients. Conclusions: The findings connect that the pathogenesis of SCZ may have a correlation with altered levels of antioxidants, MDA, macro‐minerals, and trace elements.